THU0456 THE "JOINT CRITERIA" FOR FIBROMYALGIA DIAGNOSIS IN RHEUMATOID ARTHRITIS PATIENTS: RELIABILITY COMPARED TO THE 2010 ACR CLASSIFICATION CRITERIA FOR FIBROMYALGIA. (2nd June 2020) - Ghib, L. J.; Barcic, A.; Bilous, A. D.; Cozma, I.; Tamas, M. M.; Filipescu, I.; Felea, I.; Damian, L.; Muntean, L.; Simon, S. P.; Rednic, S.
Abstract : Background: A significant proportion of rheumatoid arthritis (RA) patients have concomitant fibromyalgia (FM) (1). Associated FM diagnosis in RA patients can determine worse treatment outcomes compared to patients without FM (1). A difference between tender joint count (TJC) and swollen joint count (SJC) ≥7, also named the "joint criteria" was proposed as being diagnostic for FM in patients with RA. The "joint criteria" were validated against the 1990 ACR Classification Criteria for FM and are easy to apply to patients with RA (2). Since then, the 2010 ACR Classification criteria for FM, which include somatic symptoms besides pain sensitivity, were developed and validated. Objectives: We aimed to determine the reliability of the joint criteria for fibromyalgia in RA compared to the ACR 2010 Classification Criteria for FM and to compare RA patients diagnosed with FM (FRA) to those without FM in terms of clinical variables. Methods: We performed a cross-sectional study on RA patients who presented in our department during a 3 months period. Tender joint count (TJC), swollen joint count (SJC), patient global assessment of disease activity (PGA) were determined. DAS28 scores were calculated using CRP. We applied the 2010 ACR Classification Criteria and the joint criteria for FM diagnosis. Kappa agreement coefficient was used to determine the reliability of the joint criteria against the 2010 ACR Classification Criteria for FM in patients with RA. Differences between groups were assessed using Mann-Whitney U test for numerical data or Chi square test for ordinal data. Results: We included 100 consecutive RA patients, 84% female, with a mean age of 57.3(12) years and mean disease duration of 14(9) years. Twenty-four patients (24%) had associated FM according to the ACR 2010 Classification Criteria and 22 (22%) patients satisfied the joint criteria for associated FM. The level of agreement between the joint criteria and the ACR 2010 classification criteria for FM was kappa=0.66, p< 0.001, with a sensitivity of 70% and a specificity of 93%. FRA patients had similar demographic and disease characteristics compared to RA patients. Patients with FRA according to the joint criteria had significantly higher PGA, DAS28, and HAQ scores, but similar CRP values and SJC compared to RA patients (Table 1 ). Conclusion: The joint criteria are diagnostic for FM in RA patients with moderate reliability compared to the ACR 2010 Classification criteria. When diagnosed with the joint criteria, FRA patients have higher disease activity scores despite having similar clinical and laboratory inflammatory markers compared to RA patients. References: [1]Wolfe F, Michaud K. Severe rheumatoid arthritis (RA), worse outcomes, comorbid illness, and sociodemographic disadvantage characterize RA patients with fibromyalgia. J Rheumatol. 2004;31(4):695–700. [2]Pollard LC, Kingsley GH, Choy EH, Scott DL. Fibromyalgic rheumatoid arthritis and disease assessment. Rheumatology 2010;49(5):924–8. Disclosure of Interests: None declared